Analysis of the Dynamics of Physiological Indicators during the Recovery Period of Physiological Activity of Organisms after Covid-19" (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The problem presented in this paper was to investigate the clinical analysis of the physiological activity of organisms during the recovery period after COVID-19. The majority of patients recover spontaneously or with acute-phase management, healthcare providers confronted with the long-term effects of COVID-19, known as "post-acute COVID-19 syndrome," which encompasses a wide range of symptoms.